2016
DOI: 10.7314/apjcp.2016.17.3.1411
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilia in Pleural Effusions: a Speculative Negative Predictor for Malignancy

Abstract: Background: Eosinophilic pleural effusion (EPE) is an eosinophil count more than 10% on cytology of pleural samples. Recently, it was reported that malignancy had been the most prevalent cause inducing EPE. Therefore, we conducted an analysis on the prevalence and etiology of EPE and investigated the relationship between EPE and malignancy. Materials and Methods: Data for pleural cell differential count from patients receiving thoracentesis during the period from January 2008 to December 2013 were compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
(27 reference statements)
2
5
0
Order By: Relevance
“…The cumulative incidence of malignancy among EPEs has gradually increased from 7% to 25% over the last 4 decades (2). The current studies confirmed that malignancy was the most common etiology related to EPE (ranging from 22.7% to 40.1%) (2,7,13,18,22). The tendency may be explained by the development of diagnostic technology, improved diagnostic awareness, disparity of study population, or various disease spectrum over time.…”
Section: Incidence Of Mepesupporting
confidence: 66%
See 2 more Smart Citations
“…The cumulative incidence of malignancy among EPEs has gradually increased from 7% to 25% over the last 4 decades (2). The current studies confirmed that malignancy was the most common etiology related to EPE (ranging from 22.7% to 40.1%) (2,7,13,18,22). The tendency may be explained by the development of diagnostic technology, improved diagnostic awareness, disparity of study population, or various disease spectrum over time.…”
Section: Incidence Of Mepesupporting
confidence: 66%
“…The likelihood of malignancy was only 7% when an eosinophil count was more than 32% (2). Similarly, Chu et al (22) found that eosinophil count in pleural effusion was a speculative negative predictor for malignancy in patients with EPE when eosinophils exceeded 15%. The analysis of Krenke et al (7) revealed that an eosinophil percentage of 40% was the most accurate cut-off level to differentiate between malignant and nonmalignant EPE, which supported the study by Kuhn et al (3) who suggested that eosinophils exceeded 50% in the pleural fluid possessed the strongest negative predictability towards malignancy.…”
Section: Prognostic Significance Of Mepementioning
confidence: 88%
See 1 more Smart Citation
“…The percentages were similar to those in previous studies, which reported 12.6% [ 4 ] and 10% [ 2 ], but higher than those in two other studies, which indicated 5–8% [ 2 ] and 7.2% [ 7 ]. However, Chu FY found that the morbidity of EPE was only 2.9% [ 6 ]. The discrepancy may be attributed to different populations, epidemic characteristics, test methods or the timing of pleural fluid collection.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent systematic review that included 687 cases of eosinophilic PEs, the most frequent causes were neoplasms (26%), idiopathic (25%), parapneumonic (13%), blood or air in the pleural cavity (13%), tuberculosis (7%), and transudates (7%), among a variety of additional causes 33 . As the percentage of eosinophils in the PF increases (e.g., > 30%), the probability of a neoplasm decreases while the probability of idiopathic causes increases 33,34 . For instance, neoplasms only explained 7% of the PEs with eosinophil counts > 32% in the aforementioned systematic review 33 .…”
Section: Eosinophilic Pementioning
confidence: 99%